0134 Assessment of Soft Palate Muscle Fatigue and its Effect on Velopharyngeal Upper Airway Dynamics. (27th April 2018) - Li, W; Gakwaya, S; Sériès, F
Abstract: Introduction: Velopharynx is the most collapsible segment of the upper airway (UA), thus soft palate muscles are crucial for maintaining UA patency. This study aimed to investigate the fatigability of soft palate muscles and to quantify its effects on velopharyngeal UA dynamic properties in patients with obstructive sleep apnea (OSA) and control subjects. Methods: 14 OSA (AHI > 10 /h) and 5 control subjects were recruited to perform a soft palate fatiguing protocol, in which repetitive intra-oral positive pressure were performed during cheek-bulging maneuver while wearing a sealed-mouth-piece with jaw kept open and without disturbance of nasal breathing. Sustained maximal bulging pressure (MBP) were developed for 5 sec every 10 sec until the peak pressure couldn't reach 85% of baseline MBP for 2 consecutive times. Instantaneous airflow and velopharyngeal pressure were assessed in response to phrenic nerve magnetic stimulation performed before, and after the fatiguing protocol. UA closing pressure (Pcrit) was estimated by modeling the flow/pressure relationship in response to phrenic twitches. Results: Compared to the control and less-severe OSA (AHI: 10–20 /h), the endurance time and muscle total work for the fatiguing trial were lower in more-severe OSA (AHI>20 /h) group ( p < 0.05). The fall in the maximal mean pressure (MMP) from the beginning to the end of the fatiguing trial tended to be higher in more-severe OSA than control. In less-severe OSA patients, the Pcrit at baseline was lower than more-severe OSA (-13.3 ± 1.8 cm vs. -6.6 ± 2.6 H2 O, p < 0.05), and the UA resistance tended to increase early after the fatiguing trial compared to its baseline (5.3 ± 5.2 vs. 2.9 ± 1.7 cmH2 O·l −1 ·s −1, p =0.09). The latter was not observed in more-severe OSA patients or control. Conclusion: The cheek-bulging maneuver can induce soft palate muscle fatigue, which was more prominent in more-severe OSA patients and could further alter UA patency at the velopharyngeal level. Less-severe OSA patients are more prone to increase velopharyngeal resistance following soft palate muscle fatigue. Support (If Any): Fondation JD Bégin de l'Université Laval and Fondation IUCPQ